DAGESTAN IN THE ARABIC-PERSIAN GEOGRAPHIC WORKS OF THE FIRST HALF OF THE 13TH CENTURY - Timohin, Dmitrij Mihajlovic (History, Archeology and Ethnography of the Caucasus, 2021)
The Arabic-Persian geographic works of the first half of the 18th century are of little value in reconstructing the history of the North Caucasus. On the one hand, this can be explained by the dependence of such material on earlier Arabic-Persian monuments: we often observe repetition of information, either fully or partially. In this regard, researchers turn to earlier texts and, to a lesser extent, consider data from the text of the first half of the 13th century. On the case of three geographic works written in the period under question, the present paper attempts to demonstrate features of information about Dagestan in the context of a particular work, as well as to identify the historiographic continuity. What is more important is to highlight those plots that the authors below included in their own texts, to show what specific information on the history of Dagestan they considered important. For our study, we have selected both relatively well-known and widely used monuments, such as “Mu’jam al-Buldān” (“Dictionary of Countries”) by Yaqut al-Hamawi, as well as less popular texts – an anonymous work “Aja’ib ad-Dunya” (“Wonders of the World”) and “Jahan-nameh” (“Book About the World”) by Najib Bakran. The study focuses on the last two texts and the information they contain; however, we also try to characterize the valuable information contained in Mu’jam al-Buldān. We hope that our study will raise interest to both Arabic-Persian works mentioned here and the issue of reflecting the history of Dagestan in relatively late sources. Moreover, the very logic of including certain information on the history of the region, both in the works of the first half of the 13th century and in later texts, deserves, as we believe, special attention.
Keywords: muslim geographical works; Dagestan; Yakut al-Khamavi; the Caucasus; the Sasanians; 'Aja'ib ad-dunya; Najib Bakran.